Electrostatic interactions mediate the nucleation and growth of a bacterial functional amyloid - Bhoite, Sujeet S.; Kolli, Divya; Gomulinski, Mark A.; Chapman, Matthew R. (Frontiers in Molecular Biosciences, 2023)
Bacterial biofilm formation can have severe impacts on human and environmental health. Enteric bacteria produce functional amyloid fibers called curli that aid in biofilm formation and host colonization. CsgA is the major proteinaceous component of curli amyloid fibers and is conserved in many gram-negative enteric bacteria. The CsgA amyloid core consists of five imperfect repeats (R1-R5). R2, R3, and R4 have aspartic acid (D) and glycine (G) residues that serve as “gatekeeper” residues by modulating the intrinsic aggregation propensity of CsgA. We characterized the impact of gatekeeper residues in modulating Citrobacter youngae CsgA aggregation kinetics. We report that in Citrobacter youngae CsgA, certain arginine (R) and lysine (K) residues act as gatekeeper residues. We also demonstrate a mechanism of gatekeeping wherein R and K residues electrostatically interact with negatively charged D residues, tempering CsgA fiber formation. Using mutational studies, salt-mediated charge screening, and varying pH conditions, we show that the nucleation and fiber growth rates of CsgA are modulated by the charge state of R, K, and D residues, suggesting that electrostatic interactions are implicated in gatekeeping function.